When UTAUT2 meets design thinking mindset: Exploring e-learning champions? Adoption of blended learning at EMU - Issufo, Vali (School of Education, 2025)
Blended learning has increasingly been recognised as an effective approach to enhance student success in higher education, and to make this possible, educational technologies are crucial. Despite significant improvements to ICT infrastructure, staff training programs and help desk support, uptake differs considerably across contexts (Mohan et al., 2020) and scholars (Sherman & Howard, 2012; Taherdoost, 2018) suggest that motivation is at the core of technology acceptance. This study seeks to understand the factors motivating lecturers to accept blended learning at Eduardo Mondlane University (EMU) in Mozambique, by following a group of three lecturers who have been thriving in adopting blended learning and are eager to support others in their adoption of blended learning as well, designated in the study as "blended learning champions". The study was initially framed by the unified theory of acceptance and use of technology (UTAUT2) - a model that, through a combination of constructs such as performance expectancy, social influence, and facilitating conditions, has been used to understand factors influencing an individual's acceptance and use of technology (Venkatesh et al., 2012). Historically, using theories such as UTAUT2, technology acceptance has been understood through statistical analysis of large quantitative data sets. However, this study focuses on the stories told by three "blended learning champions" drawing from qualitative in-depth interviews. Using participatory action techniques (Bozalek & Biersteker, 2010), such as Rivers of Life and Community Mapping over six individual interviews and a focus group, I elicited detailed narrative data, which appeared to go beyond the UTAUT2 model. Thematic analysis was employed to identify key patterns and insights from this qualitative data. Thus, later, I turned to research on design thinking mindsets (Gachago et al., 2017), which looks at characteristics of people that help them approach problems in unique and innovative ways, such as empathy, curiosity, collaborativeness and others. The study shows that for these blended learning champions, the availability of ICT infrastructure, training, helpdesk support and so on are, as expected, Facilitating Conditions. However, what is interesting is that, when faced with challenges, blended learning champions tend first to look inward for solutions. The study also reveals that they are well aware that adopting new technologies and methodologies will be challenging, which is why, in terms of Effort expectancy, they engage with one problem at a time. Moreover, blended learning champions also feel confident that, by gradually adopting blended learning, their performance will improve (Performance expectancy), while, at the same time, improving their work-life balance. Blended learning champions understand that experimenting and failing are part of the learning process. Unlike most studies with UTAUT2, Social influence was found to have less impact; these blended learning champions feel unburdened by peer pressure and generally feel comfortable whenever they do not know what to do or commit mistakes while using technology. All of these are elements of a design thinking mindset or culture. This research contributes to a local understanding of the factors motivating lecturers' uptake of blended learning. Thus, to boost blended learning uptake, institutions should not only focus on Facilitating Conditions such as technological infrastructure and staff training, but also create a less pressured and more empathetic environment where lectures feel at ease with what they do not know, are presented with a modest but steady adoption process, and where educational technologies contribute to the improvement of their work-life balance. As such, the study confirms the theory underpinning the design thinking mindset in relation to what motivates the blended learning champions, and this contributes to creating a bridge between design thinking and technology acceptance research. Finally, the study has highlighted the importance of the individual context in UTAUT2 research. How to create such a culture in the current climate of a neoliberal university remains an important question, which might be a topic of further research.